2023
DOI: 10.18502/ijph.v52i8.13399
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Non-Alcoholic Fatty Liver Disease in Iranian Children and Adult Population: A Systematic Review and Meta-Analysis

Soheil Hassanipour,
Ehsan Amini-Salehi,
Farahnaz Joukar
et al.

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is the world's most common etiology of chronic liver disease. In this systematic review and meta-analysis, we estimated the prevalence of NAFLD in the Iranian children and adult population. Methods: A comprehensive search of five international databases, including PubMed, ISI/WOS, ProQuest, Scopus, and Google Scholar, was done from inception to Nov 2022. Studies on NAFLD patients and their risk factors were selected for meta-analysis. The quality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…Outcome data are summarized in Table 1 . As interpreted, 52 (26.9%), 9 (4.7%), and no participants had grade I, grade II, and grade III NAFLD, respectively; the crude prevalence of NAFLD for both women (RR [95% confidence interval (CI)] 1.04 [0.77, 1.39], p = 0.74) and men (RR [95% CI] 0.99 [0.49, 1.77], p = 0.99) with MS as calculated in the present study were comparable to that reported for the general Iranian population in a recent meta-analysis involving more than 30 thousand adults 13 . An older meta-analysis study 14 reported similar values as well.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Outcome data are summarized in Table 1 . As interpreted, 52 (26.9%), 9 (4.7%), and no participants had grade I, grade II, and grade III NAFLD, respectively; the crude prevalence of NAFLD for both women (RR [95% confidence interval (CI)] 1.04 [0.77, 1.39], p = 0.74) and men (RR [95% CI] 0.99 [0.49, 1.77], p = 0.99) with MS as calculated in the present study were comparable to that reported for the general Iranian population in a recent meta-analysis involving more than 30 thousand adults 13 . An older meta-analysis study 14 reported similar values as well.…”
Section: Resultssupporting
confidence: 82%
“…An older meta-analysis study 14 reported similar values as well. Nevertheless, caution is advised in interpretation of this comparison, as different diagnostic tools may have been utilized in the present study and the ones included in the meta-analysis 13 . Furthermore, based on the values put forth by the American College of Gastroenterology (ACG) 15 , 47/160 (29.4%) of the women, and 14/33 (42.4%) of the men (61/193 [31.6%] of the total pwMS) had elevated ALT levels, of whom, 17 (27.9%) had grade I, and 4 (6.5%) had grade II NAFLD (Pearson Chi 2 : 0.82, p = 0.66).…”
Section: Resultsmentioning
confidence: 99%
“…NAFLD is the common cause of asymptomatic elevated liver enzymes [ 43 ]. According to a recent meta‐analysis, the prevalence of NAFLD in women was about 30% [ 44 ]. In a study among the Iranian population, the risk of fatty liver diseases increased among subjects with IR [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…159 Compared with individuals with MUO, those with MHO often have a higher proportion of lower-body SWAT, which is associated with a lower risk of sudden CVDs, even with the same total body fat content. 160 Higher expression of genes are involved in fat production pathways, such as cluster of differentiation 36 (CD36), 161 glucose transporter 4 (GLUT4), 162 carbohydrate response element-binding protein (ChREBP), 163 fatty acid synthase (FASN), 164 and mannosyl (alpha-1,3-)-glycoprotein beta-1,2-N-acetylglucosaminyltransferase I (MGAT1). 165 The expression of these genes is positively correlated with insulin sensitivity.…”
Section: Swat and Mhomentioning
confidence: 99%